(untitled) (International Journal of Engineering and Computer Science, 2017)
The increasing number of devices within the IoT is raising concerns over the efﬁciency and exploitability of existing authentication methods. The weaknesses of such methods, in particular passwords, are well documented. Although alternative methods have been proposed, they often rely on users being able to accurately recall complex and often unmemorable information. With the profusion of separate online accounts, this can often be a difﬁcult task. The emerging digital remembrance concept involves the creation of a repository of remembrance speciﬁc to individuals. We believe this abundance of personal data can be utilized as a form of authentication. In this paper, we propose our digital remembrance based two-factor authentication mechanism, and also present our promising evaluation results. Keywords—Digital remembrance, authentication, IoT, security